Proton Holdings Berhad Strategies For The Ist National Automobil Company - Narayanasamy, Logeswary (2005)
Proton has made a major step in upgrading its engineering capabilities with the acquisition of Lotus Group International Limited (Lotus) and partnership with various group such as Petronas, Modenas, Phoenix and recently with Volkswagen AG. Proton has the intellectual property for four platforms and plans to sell these platform to collect royalties.